2003
DOI: 10.1021/bi034850d
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Membrane Binding Mode of the C2 Domain of PKCε

Abstract: PKCepsilon is a member of the group of novel PKCs that contain a C2 domain located in their N-terminal region. On the basis of recent structural studies, a series of mutants were prepared to increase our knowledge of the mechanism of the phospholipid binding site of this domain. The results revealed that this domain preferentially binds to phosphatidic acid- and phosphatidylserine-containing vesicles. Although the increase in affinity was linear in the case of phosphatidic acid, it became exponential when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 27 publications
3
37
0
1
Order By: Relevance
“…These results suggest that the inositol ring is not buried in the cavity of the mCPK-C2 domain, and therefore the C2 domain binds lipids in a different fashion than the PX domain. This kind of binding mode is primarily defined by the ionic interaction between lysine side chains and phosphates (as sulfate observed in structure), which is consistent with the observation for other C2 domains that bind to PA and/or PS within SytI and PKC␤ (10,(23)(24)(25)(26).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These results suggest that the inositol ring is not buried in the cavity of the mCPK-C2 domain, and therefore the C2 domain binds lipids in a different fashion than the PX domain. This kind of binding mode is primarily defined by the ionic interaction between lysine side chains and phosphates (as sulfate observed in structure), which is consistent with the observation for other C2 domains that bind to PA and/or PS within SytI and PKC␤ (10,(23)(24)(25)(26).…”
Section: Resultssupporting
confidence: 87%
“…On the other hand, an increasing number of C2 domains, including the C2 domains of class II PtdIns 3-kinases, were identified as Ca 2ϩ insensitive due to the lack of the conserved aspartate residues necessary for Ca 2ϩ binding. The C2 domains in other proteins were also shown to bind specifically to acidic phospholipids such as phosphatidic acid (PA) and phosphatidylserine (PS) (10,(23)(24)(25)(26). However, the contribution of the lipid binding ability of the C2 domains to the physiological function of those C2 domain-containing proteins is still not clear.…”
mentioning
confidence: 99%
“…PA can be generated rapidly via hydrolysis of PC by phospholipase D or by phosphorylation of diacylglycerol by diacylglycerol kinases. Notably, PA has been shown to regulate both localization and function of several effectors (26), which include important signaling regulators such as Raf-1 (27), protein kinase C epsilon (28) and sphingosine kinase 1 (29). However, although several PA binding sequences have been identified, a signature binding motif for PA has yet to be identified (26,30).…”
mentioning
confidence: 99%
“…However, the structure of the C2 domain of the epsilon family of PKCs including PKC Apl II is considerably different (11,15,33,35,45), and these C2 domains do not bind phosphotyrosine (10,42). It has been reported that the C2 domain of PKCε can bind to phospholipids, especially phosphatidic acid (PA), and that PA binding to the C2 domain of PKCε is required for translocation (11,18). However, the amount of PA required to bind to the C2 domain is high compared to that for the Ca 2ϩ -dependent binding of the C2 domains of cPKCs to PS (11,16,25,45).…”
mentioning
confidence: 99%
“…The C2 domain of PKC␦ binds to phosphotyrosine, allowing for the regulation of the kinase (2, 41, 51). However, the structure of the C2 domain of the epsilon family of PKCs including PKC Apl II is considerably different (11,15,33,35,45), and these C2 domains do not bind phosphotyrosine (10,42). It has been reported that the C2 domain of PKCε can bind to phospholipids, especially phosphatidic acid (PA), and that PA binding to the C2 domain of PKCε is required for translocation (11,18).…”
mentioning
confidence: 99%